Identification of Risk Factors Affecting PPP Waste-to-Energy Incineration Projects in China: A Multiple Case Study. (1st August 2018) - Liu, Yong; Sun, Chenjunyan; Xia, Bo; Liu, Sai; Skitmore, Martin
Abstract : Waste-to-energy (WTE) incineration technologies are considered an effective solution for sustainable and efficient municipal solid waste (MSW) disposal in China, and the public-private partnership (PPP) arrangement has been widely used to construct and operate WTE incineration projects. However, PPP WTE incineration projects in China are affected by numerous risks due to the long concession period, various participants, and other factors commonly involved in PPPs, resulting in a number of failures. In light of the pivotal role that risk identification, analysis, and response play in the successful development of PPP WTE incineration projects, this paper presents a multiple case study to identify the risk factors involved in China by drawing on experience from the real-life risk events of 35 PPP WTE incineration plants. 18 risk factors are identified; the most critical of which being public opposition risk, environmental pollution risk, government decision-making risk, a defective legal and regulatory system, and MSW supply risk. The results of the study provide a solid foundation for the future risk analysis, risk allocation, and risk response of PPP WTE incineration projects, and shed light on performance improvement of the PPP WTE incineration projects as well as the development of the PPP WTE industry in China.